2020
DOI: 10.1002/jib.602
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming technical barriers to brewing with green (non-kilned) malt: a feasibility study

Abstract: Brewing using enzyme rich ‘green’ (germinated, but not kilned) malt has the potential to unlock considerable energy savings in the malting and brewing chain. This paper examines the major quality issues associated with green malt, by monitoring lipoxygenase (LOX) activity and S‐methyl methionine (SMM) levels through a micromalting cycle both with and without rootlets after 48 h of germination. The data suggest that rootlets are a major concern when brewing with green malt and that their influence on wort and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…Thus, future studies should be directed to the oxidation of unsaturated fatty acids to further elucidate why THFA increased when brewing with kilned malt, but contrary to expectations, not when using green malt. Previous research from our group ( 26 ) had indicated that re‐steeping of green malt in water for an hour was an effective means to reduce the LOX activity of green malt by around 50%. Accordingly, it was decided to assess the quality impact of this putative process at pilot scale, including the re‐use of re‐steep water as mashing liquor in the green malt brewing process in order to minimise overall water usage in the chain.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, future studies should be directed to the oxidation of unsaturated fatty acids to further elucidate why THFA increased when brewing with kilned malt, but contrary to expectations, not when using green malt. Previous research from our group ( 26 ) had indicated that re‐steeping of green malt in water for an hour was an effective means to reduce the LOX activity of green malt by around 50%. Accordingly, it was decided to assess the quality impact of this putative process at pilot scale, including the re‐use of re‐steep water as mashing liquor in the green malt brewing process in order to minimise overall water usage in the chain.…”
Section: Resultsmentioning
confidence: 96%
“…The malts used for the preparation of the beers were analysed for trihydroxy fatty acids (THFA) levels. Clearly, green malt has a higher lipoxygenase (LOX) activity compared to kilned malt ( 26 ) ; a major threat for beer flavour and stability. The determined contents of THFA in the malts used for this study were significantly lower in kilned malt (39.6 ± 9.9 mg/kg, dry basis) compared to green malt (68.3 ± 4.5 mg/kg, d.b.).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that along with ACA (K a = 485 × 10 3 ), Meth (K a = 50 × 10 3 ) and 3MB (K a = 29 × 10 3 ) showed higher affinity toward HSO 3 − compared to PA (K a = 17 × 10 3 ), 2MP (K a = 2.8 × 10 3 ), 2MB (K a = 2.6 × 10 3 ), or Fur (K a = 0.1 × 10 3 ). Higher values indicate an increased affinity toward nucleophiles [14,15].…”
Section: Influence Of Aldehyde Structure On Occurrence In a Bound Statementioning
confidence: 99%
“…For example, this can be done in the so-called nonenal potential. Hereby, the capacity of a wort to produce (E)-2-nonenal (T2N) and, since recently, also hexanal (Hex) is assessed [14,15]. Using 4-vinyl pyridine (4VP), Baert et al developed a method to release bound state aldehydes from these bound forms through a pH shift and trapping of cysteine [16,17].…”
Section: Introductionmentioning
confidence: 99%